Tandem-L: An Innovative Bistatic SAR Mission for Monitoring Earth′s Dynamic Processes - Zink, Manfred; Moreira, Alberto; Krieger, Gerhard; Bachmann, Markus; Balzer, Wolfgang; Borla-Tridon, Daniela; Eineder, Michael; Hajnsek, Irena; Huber, Sigurd; Klenk, Patrick; Maurer, Edith; Papathanassiou, Konstantinos; et al. (CEOS SAR Workshop on Calibration and Validation (CEOS SAR CalVal), 2017)
Tandem-L is a proposal for a highly innovative L-band SAR mission for the systematic observation of dynamic processes on the Earth's surface with hitherto unparalleled quality and resolution. Thanks to the novel imaging techniques and the vast recording capacity of up to eight terabytes/day, it will provide vital information for solving pressing scientific questions in the biosphere, geosphere, cryosphere, and hydrosphere and will make an essential contribution for a better understanding of the Earth system and its dynamics. The Tandem-L mission concept is based on the use of two SAR satellites operating in L-band with variable formation flight configurations. It is distinguished by its high degree of innovation. Examples are the polarimetric SAR interferometry (PolinSAR) for measuring forest height, multi-pass coherence tomography for determining the vertical structure of vegetation and ice, the utilization of the latest digital beamforming techniques in combination with a large deployable reflector for increasing the swath width and imaging resolution, as well as the formation flight of two cooperative radar satellites with adjustable baselines for single-pass interferometry . The systematic acquisition concept is based on two imaging modes: the 3-D structure mode with a bistatic radar operation and the Deformation imaging mode with differential SAR interferometry (DinSAR), both allowing the achievment of the specified mission objectives. In this presentation, we provide an overview of the current status of this innovative mission and its main application areas.
DLR Import::2019-04-03